“And Then I Got Pregnant”: Early Childbearing and the First Nations Life Course - Cooke, Martin (International Indigenous Policy Journal, 2013)
One of the characteristics of the life courses of Aboriginal youth is a greater likelihood of becoming a parent at young ages, at least relative to other youth. Young parenthood is often portrayed negatively, in terms of the implications for later education and employment. However, these effects depend greatly on the context of childbearing, including the sources of available support. In this paper we make use of exploratory qualitative life course interview data with a sample of First Nations living in Canadian cities to investigate the circumstances around early childbearing, including sources of support and strategies for managing this transition, its meaning from the perspective of parents themselves, and the potential implications for their later lives.